2015
DOI: 10.9789/2175-5361.2015.v7i3.2717-2725
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypertensive syndromes particular of pregnancy (GHS)

Abstract: Objective: identifying the prevalence of Specific Hypertensive Syndromes of Gestation and outline the epidemiological profile of pregnant women. Method: a retrospective research, conducted in medical records of women admitted to the obstetric clinic of the University Hospital Lauro Wanderley, João Pessoa/PB, between January 2009 and December 2010. Data were collected through a questionnaire with closed questions, and analyzed descriptively. Ethical observances in research involving human subjects were contempl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 4 publications
2
13
0
7
Order By: Relevance
“…The obtained result in this study was equipped to the found by Brito et al [27], in which 77.1% of the childbirth occurred by cesarean. Likewise, according to the study of Silva et al [16], which analyzed the data from 1999 to 2013 in Brazil, there were a decline on the normal childbirth and an increasing of 63.68% on the cesarean occurrences.…”
Section: R S Souza Et Alsupporting
confidence: 64%
“…The obtained result in this study was equipped to the found by Brito et al [27], in which 77.1% of the childbirth occurred by cesarean. Likewise, according to the study of Silva et al [16], which analyzed the data from 1999 to 2013 in Brazil, there were a decline on the normal childbirth and an increasing of 63.68% on the cesarean occurrences.…”
Section: R S Souza Et Alsupporting
confidence: 64%
“…However, in certain situations, with defined risks, there may be variations that favor unfavorable outcomes for the mother and fetus. 1 Thus, the World Health Organization (WHO) determines maternal death as that which occurred during pregnancy or up to 42 days after regardless of location or duration. 2 During the year 2015, around 300 thousand maternal deaths occurred worldwide, most of them in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…2 Thus, hypertensive syndromes can present as chronic hypertension, when their occurrence precedes gestation or presents before 20 weeks gestation; pre-eclampsia, when hypertension and proteinuria occur after the 20th week; eclampsia, characterized by tonic-clonic seizures or coma in a woman with no epilepsy or other convulsive causes; preeclampsia with overlapping hypertension, defined as pre-eclampsia in chronic hypertensive or with renal disease and gestational hypertension without proteinuria. 1,5 In addition to these types, the hypertensive syndrome may present as a multisystem clinical manifestation, involving several organs, in the form of HELLP syndrome, derived from the English Hemolysis, Elevated Liver enzymes. Low Platelets.…”
mentioning
confidence: 99%
See 2 more Smart Citations